Acquired unilateral nevoid telangiectasia and acquired port-wine stain: one disease or distinct diseases? - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Telangiectasia is clinically a reddish-blue linear lesion that disappears under fingers pressure; more telangiectases can be grouped with each other while maintaining their individuality. On the other hand, port-wine stain is a reddish-blue, flat stain of uniform color in which isolated vessels can not be seen to the naked eye. Both nevoid telangiectases and port-wine stain can be congenital or acquired. In this work starting from two clinical cases of unilateral nevoid telangiectasia and acquired port-wine stain, both acquired in the prepubescent age, we analyze the differences and similarities between the two diseases.